An introduction to nuclear medicine - Ballinger, James R. (Henry Stewart Talks, 2021)
What is nuclear medicine?, Radiopharmaceuticals, Radiation and detection, Theranostics, Clinical uses of SPECT, Clinical uses of PET, The future of nuclear medicine